Sistematika dan Pemetaan Konsep Ketuhanan Agama-Agama Lokal di Indonesia: Studi Kasus Agama Sunda Wiwitan, Agama Kaharingan, dan Agama Towani Tolotang - Agus Himmawan Utomo; Galuh Nur Fattah (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Abstract: Indonesia has an invaluable cultural heritage, one of which is the existence of various indigenous religions that are widespread throughout the country. Despite their significant number, their presence is oftendisregarded by the majority of society who have adopted formal religions that are recognized by the state. Followers of indigenous religions are often deemed misguided by formal religion practitioners because theyperceive these ancestral religions as worshiping entities other than God, as recognized by their own religious tradition. This is exacerbated by the government's attempt to integrate indigenous religions into one of therecognized formal religions, which poses a threat to the preservation of the teachings and religious practices of indigenous religion followers as their religious practices will inevitably be influenced by the standardizations of the formal religions, which are essentially religions of foreign origin. All forms of discrimination arise, among others, from the weakness or inability of indigenous religion followers to explain their theological systems and concepts of divinity. Therefore, this study attempts to explain the concept of divinity in indigenous religions by using three casestudies: Sunda Wiwitan, Kaharingan, and Towani Tolotang. The results of this study show that there are authentic characteristics of divinity in each of the studied indigenous religion systems, which are specifically categorized as henotheism and Animism-Dynamism.Keyword: Indigenious Religions, Concept of Divinity, Henotheism, Animism-Dynamism